2010
DOI: 10.1590/s1806-83242010000200007
|View full text |Cite
|
Sign up to set email alerts
|

The effect of irrigation solutions on the apical sealing ability in different root canal sealers

Abstract: The aim of this study was to assess the effect of three root canal irrigation solutions on the apical sealing ability of three root canal obturation materials: gutta-percha/AH plus or MM-seal and Resilon/ Epiphany SE. A total of 100 teeth with single straight root canals were randomly divided into three equal groups of 30 samples each, with the other 10 teeth (5 positive and 5 negative) used as controls. Each irrigation group was divided into three groups according to the use of three different root canal obtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 27 publications
4
22
0
1
Order By: Relevance
“…6,13,14 MM-Seal (Micro-Mega, Besançon, France), a similar epoxy resin-based polymer, is composed of ethylene glycol salicylate, calcium phosphate, bismuth subcarbonate, and oxide components, thus presenting satisfactory physical and chemical properties of flow (FL) into lateral canals, RD, biocompatibility, and working time. Bodrumlu et al, 15 Bodrumlu et al, 5 and Poggio et al 16 reported that this root canal sealer has a bond strength comparable with that of AH Plus. However, no studies in the current literature provide an evaluation of its physicochemical properties.…”
Section: 23mentioning
confidence: 98%
See 3 more Smart Citations
“…6,13,14 MM-Seal (Micro-Mega, Besançon, France), a similar epoxy resin-based polymer, is composed of ethylene glycol salicylate, calcium phosphate, bismuth subcarbonate, and oxide components, thus presenting satisfactory physical and chemical properties of flow (FL) into lateral canals, RD, biocompatibility, and working time. Bodrumlu et al, 15 Bodrumlu et al, 5 and Poggio et al 16 reported that this root canal sealer has a bond strength comparable with that of AH Plus. However, no studies in the current literature provide an evaluation of its physicochemical properties.…”
Section: 23mentioning
confidence: 98%
“…Although gutta-percha combined with the sealer AH Plus remain the most widely used materials in the filling procedure; 1, 3,4,5,6,7,8,9 numerous techniques and materials with different physicochemical and biological properties have also been developed. 2,3,8,9,10 Root canal sealers can be classified according to their composition as zinc oxide and eugenol-based sealers; sealers containing calcium hydroxide; glass Rafael Verardino de CAMARGO (a) Yara Terezinha Corrêa SILVA-SOUSA (b) Rodrigo Presotto Ferreira da ROSA (a) Jardel Francisco MAZZI-CHAVES (a) Fabiane Carneiro LOPES (a) Liviu STEIER (c) Manoel Damião SOUSA-NETO (a) ionomer, epoxy resin, and methacrylate resin-based sealers; or bioceramic and silicone-based sealers 1,3,[7][8][9] .…”
Section: 23mentioning
confidence: 99%
See 2 more Smart Citations
“…Several methods aimed at detecting leakage have already been described in the literature, such as the conductometric technique, 2 fluid filtration, 3,4 radioisotopes, 5 bacterial penetration, 6 the electrochemical test, 7 and the use of dyes. 8,9 However, all these methods have yielded controversial results, and have therefore been widely criticized. 7,8,10,11 Some studies have presented improvements to leakage assessment methods.…”
Section: Introductionmentioning
confidence: 99%